Carotid resection and reconstruction associated with treatment of head and neck cancer - Kroeker, Teresa R. (Baylor Health Care System, 2011)
Patients with head and neck cancer may experience carotid artery involvement. We present a series of 10 patients, all with stage IVB disease, who required carotid resection and reconstruction to achieve a complete resection. Nine of the 10 patients had previous radiation treatment to the neck. Six died of distant disease, and three died of other causes with no local or regional recurrences. Carotid resection and reconstruction can be done safely, achieving local and regional control.